2021
DOI: 10.1016/s2542-5196(21)00026-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambient carbon monoxide and daily mortality: a global time-series study in 337 cities

Abstract: Background Epidemiological evidence on short-term association between ambient carbon monoxide (CO) and mortality is inconclusive and limited to single cities, regions, or countries. Generalisation of results from previous studies is hindered by potential publication bias and different modelling approaches. We therefore assessed the association between short-term exposure to ambient CO and daily mortality in a multicity, multicountry setting.Methods We collected daily data on air pollution, meteorology, and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…PM2.5 and ozone are the most prominent pollutants that have been quantitatively associated with premature deaths 18,19 , though adverse health effects have also been reported for other pollutants 20,21 . Most studies have shown that the premature deaths attributed to O3 exposure are much fewer than those attributed to PM2.5 [22][23][24] .…”
Section: S12mentioning
confidence: 99%
“…PM2.5 and ozone are the most prominent pollutants that have been quantitatively associated with premature deaths 18,19 , though adverse health effects have also been reported for other pollutants 20,21 . Most studies have shown that the premature deaths attributed to O3 exposure are much fewer than those attributed to PM2.5 [22][23][24] .…”
Section: S12mentioning
confidence: 99%
“…Previous studies have reported that the relationship between air pollutants and mortality is approximately linear without obvious threshold [19,20]. The exposure-response relationship is widely used to evaluate the health impact by many researchers [9,21].…”
Section: Estimation Of the Mortality Effects Of A Unit Change In Daily Pollutant Concentrationsmentioning
confidence: 99%
“…The severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) pandemic identified in 2019 (COVID- 19) was reported to have caused 144,358,956 confirmed cases of coronavirus disease worldwide by 24 April 2021 [1]. The pandemic has changed almost every aspect of life worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is formed by incomplete combustion of fossil fuels and is ubiquitous in ambient air. The adverse health effects of very high CO concentrations, such as CO poisoning and cardiovascular deaths, are well documented; see e.g., Liu et al (2018); Kinoshita et al (2020); Chen et al (2021). Thus, air quality prediction is vital to management of human health, especially the respiratory system.…”
Section: Beijing Multi-site Air-quality Datamentioning
confidence: 99%